2021
DOI: 10.1016/j.nanoen.2020.105434
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the filtration efficiency and wearing time of disposable surgical masks using TENG technology

Abstract: The COVID-19 pandemic has caused an unprecedented human and health crisis. And the shortage of protective equipment, especially the personal protective disposable surgical masks, has been a great challenge. Here, we developed an effective and simple scheme to prolong the lifetime of disposable surgical masks without changing their current structure, which is beneficial to solve the shortage of personal masks. After electrifying the meltblown PP filter by the new-developed single-electrode-based sliding triboel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…3-D printing of two kinds (torturous or bifurcating) structures were analysed Reduce micron-sized particles from air at flow rates of 5 to 100 LPM at [ 56 ] Spider-net-like 2-D nanofiber (~ 30 nm) net structures were electrospun using 0.1 wt% LiCl in 4 wt% PAN/DMF High reduction (99.996%) of 0.3 µm PM were obtained at low thickness membrane of 0.4 µm with specific areal weightage of 0.68 g/m 2 [ 57 ] 3-D-printed 6 masks covers and maximized usage of one N95 fabric which can be used by single person to 6 persons. Performed user trials revealed good fit Rapid prototyping took ~ 33 min for 3-D design and printing took ~ 10 h [ 58 ] Rechargeable mask Triboelectric charge generation enhanced the filtration efficiency of disposable surgical mask and provided reusability Filtration efficiency doubled and stayed > 95% even after 10 times reuse by 80 °C disinfection [ 59 ] Various photobiocidal agents that can be regain biocide activity under sunlight after use in dark conditions Benzophenone tetracarboxylic dianhydride (BD) and chlorogenic acid (CA) exhibited highest reactive oxygen species generation [ 60 ] Comfort management Survey with 40 participants found comfort decreased with increasing pressure drop during exhalation. Different types of masks were tested Tight-fitting masks with small fans performed better than masks without fans [ 61 ] Reusable masks tested for air and water vapour permeability, thermal conductivity, and a wear trial Masks with thin fabric had good breathability.…”
Section: New Trends In Materials and Designs For Face Maskmentioning
confidence: 99%
See 1 more Smart Citation
“…3-D printing of two kinds (torturous or bifurcating) structures were analysed Reduce micron-sized particles from air at flow rates of 5 to 100 LPM at [ 56 ] Spider-net-like 2-D nanofiber (~ 30 nm) net structures were electrospun using 0.1 wt% LiCl in 4 wt% PAN/DMF High reduction (99.996%) of 0.3 µm PM were obtained at low thickness membrane of 0.4 µm with specific areal weightage of 0.68 g/m 2 [ 57 ] 3-D-printed 6 masks covers and maximized usage of one N95 fabric which can be used by single person to 6 persons. Performed user trials revealed good fit Rapid prototyping took ~ 33 min for 3-D design and printing took ~ 10 h [ 58 ] Rechargeable mask Triboelectric charge generation enhanced the filtration efficiency of disposable surgical mask and provided reusability Filtration efficiency doubled and stayed > 95% even after 10 times reuse by 80 °C disinfection [ 59 ] Various photobiocidal agents that can be regain biocide activity under sunlight after use in dark conditions Benzophenone tetracarboxylic dianhydride (BD) and chlorogenic acid (CA) exhibited highest reactive oxygen species generation [ 60 ] Comfort management Survey with 40 participants found comfort decreased with increasing pressure drop during exhalation. Different types of masks were tested Tight-fitting masks with small fans performed better than masks without fans [ 61 ] Reusable masks tested for air and water vapour permeability, thermal conductivity, and a wear trial Masks with thin fabric had good breathability.…”
Section: New Trends In Materials and Designs For Face Maskmentioning
confidence: 99%
“…It was found that the tribocharging process almost doubled the efficiency of 0.3 µm PM. They also reported that 80 °C dry heating is a suitable method to disinfect and even after 10 times reuse the filter materials exhibited > 95% filtration efficiency [ 59 ]. Si.…”
Section: New Trends In Materials and Designs For Face Maskmentioning
confidence: 99%
“…Table 4 shows the most diverse products indicated in the prevention and protection against SARS.CoV-2. Zhang et al (Zhang et al 2021b) developed an exciting method to increase the time of use and useful life of surgical masks using triboelectric nanogenerator technology (TENG). This generator can transform external mechanical energy into electrical energy based on static electricity and triboelectric effect (Fan et al 2012;Wu et al 2018).…”
Section: Personal and Collective Protective Equipment Against Covid-19mentioning
confidence: 99%
“…This generator can transform external mechanical energy into electrical energy based on static electricity and triboelectric effect (Fan et al 2012 ; Wu et al 2018 ). The method developed by Zhang et al (Zhang et al 2021b ) consists of the discharge of this generated energy using an electrode in the surgical mask, already used and decontaminated. This process allows re-energizing the layers of electrostatic filtering tissues, which generally dissipate this energy in a few hours (Lee and Kim 2020 ).…”
Section: Overview Of Nanotechnology Products For Covid-19mentioning
confidence: 99%
“…Some strategies to deal with the environmental and supply-demand challenges include, proper mask-wearing protocols, disinfecting and reusing N95 respirators, use of cloth masks with disposable inserts ( CDC, 2020 ; Dennis et al, 2020 ), and even mask allocation strategies based on different age ranges and risk levels ( Worby and Chang, 2020 ). On the one hand, face masks are considered disposable since they gradually lose their filtration efficiency ( Zhang et al, 2021 ), and become contaminated hosting sites for virus particles and microorganisms ( Zhiqing et al, 2018 ). On the other hand, up to two-thirds of the filtration efficiency is provided by the embedded electrostatic charges ( Kilic et al, 2015 ; Konda et al, 2020 ) (see Fig.…”
Section: Introductionmentioning
confidence: 99%